Software architecture based on microservices applied in aSmart Campus environment - Yamao, Eiriku (2019)
The present work is aimed to describe the microservice based architecture used in macetamascota, part of a smart campus project in Universidad de San Martin de Porres (Peru). A microservice architecture was successfully implemented in a smart campus environment to improve the self-sufficiency and sustainability of the flowers and ornamental plants inside campus. Results show the key components and interactions for a microservice architecture for smart campus, setting the groundwork for further studies and scaling into a larger city- wide implementation